PROSPEK HUKUM ISLAM DI BIDANG PENGUATAN MONETER DENGAN PEMBERLAKUAN MATA UANG DINAR DAN DIRHAM - R Fauzi (JCH (Jurnal Cendekia Hukum), 2018)
The limitation of the use of coins lies in its weight, so that since before Islam, in addition to the currency of the dinar and dirham, also apply to the trade papers and bonds (credit) for large commercial transactions. In running his government, at least the Prophet set nine policies in the field of monetary, among them are: First, let the currency of dinar and dirhams and trade notes and bonds payable. Second, the exemption of tariffs and import duties on imports of gold and silver and commodities from the Persian and Roman regions. Third, the prohibition of money accumulation (kanz). Fourth, the prohibition of stockpiling to maintain the stability of the value of money. Fifth, the prohibition of lending money (riba) which is run along with the prohibition of hoarding money (kanz) has accelerated the circulation of money directed to investment activities. Sixth, encourage interest-free loans (qardhul hasan) and profit sharing and risk sharing models. Seventh, prevent speculative activities. Eighth, increasing the production of goods and services. Ninth, the abolition of the trade monopoly of the Quraysh in Ukaz and Dul-Majaz markets after the conquest of Mecca. The removal of this monopoly improves the efficiency and distribution of better income. Effective demand and demand for money transactions increased so as to speed up the circulation of money.